VD_FINDINFO HC / 2022 / 951 vom 7. Dezember 2022 - VD Tribunal cantonal (2022)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, CONJOINT, ACTION EN MODIFICATION, MODIFICATION DES CIRCONSTANCES | 179 al. 1 CC, 229 al. 3 CPC (CH)